2002
DOI: 10.1590/s0006-87052002000200005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da época de colheita no crescimento vegetativo, na produtividade e na qualidade de raízes de três cultivares de mandioca

Abstract: RESUMOCom o objetivo de determinar o efeito da época de colheita no crescimento vegetativo, na produtividade e na qualidade de raízes tuberosas de três cultivares de mandioca (Manihot esculenta Crantz), desenvolveu-se em Araruna, Noroeste do Estado do Paraná, um experimento em área de Latossolo Vermelho Distrófico, no período de outubro de 1997 a maio de 1999. O delineamento experimental utilizado foi o de blocos completos casualizados, em esquema de parcelas subdivididas, com quatro repetições, sendo os trata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
15

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 8 publications
0
11
0
15
Order By: Relevance
“…2, 3 and 4 contrast the productive performance of the storage root dry matter for Mico, IAC 13 and IAC 14 cultivars, respectively. Leaf dry matter yield indicated that the initial reduction in the storage root yield coincided exactly with the restructuring period of the plant photosynthesis apparatus and that the later increase and stabilization was probably related to the intensification on assimilate production by the photosynthesis apparatus (Sagrilo et al, 2002). Generally, for the cultivars under study, the performance of the storage root dry matter yield followed the same yield pattern as the stem dry matter, and the values of the first were always superior to those of the latter.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…2, 3 and 4 contrast the productive performance of the storage root dry matter for Mico, IAC 13 and IAC 14 cultivars, respectively. Leaf dry matter yield indicated that the initial reduction in the storage root yield coincided exactly with the restructuring period of the plant photosynthesis apparatus and that the later increase and stabilization was probably related to the intensification on assimilate production by the photosynthesis apparatus (Sagrilo et al, 2002). Generally, for the cultivars under study, the performance of the storage root dry matter yield followed the same yield pattern as the stem dry matter, and the values of the first were always superior to those of the latter.…”
Section: Resultsmentioning
confidence: 93%
“…Rimoldi et al (2006) found that the traditional cultivars Caipira, Branca 1, Amarela 1, Amarela 2 and Fécula Branca showed high roots yields and starch contents, a good and regular cooking time, low HCN content, and also tolerance to the bacterial blight. Furthermore, Sagrilo et al (2002) assessed the performance of cassava cultivars in the Northwest Paraná at different harvest times and concluded that, for those conditions, the physiological rest period at the end of the second crop cycle was more indicated for harvest, due to the higher production of the storage root fresh and dry matter and starch. Sagrilo et al (2003) observed that the cultivars IAC 13, IAC 14 and Fécula Branca had high dry matter content in the storage roots.…”
Section: Introductionmentioning
confidence: 99%
“…However, this content is signifi cantly lower than that of conventional cassava (25-30g 100g -1 of root) (VIEIRA et al, 2008). Based on the estimated root productivity of the Manicueira 62 landrace (57.30ton ha -1 ), the yield in starch would be 2.19ton ha -1 while that a conventional 12-month-old cassava plant would be more than double (4.5ton ha -1 ) (SAGRILO et al, 2002).…”
Section: Root Compositionmentioning
confidence: 92%
“…According to Andrade et al (2011), cassava plants prunig during the dormant period increases the production of roots, which tend to present more dry mass and lower flour production at the end of the cycle. Likewise, Sagrilo et al (2002) observed that the second stage of the physiological rest of the varieties Mico, IAC 13 and IAC 14 was more beneficial to harvest than a single growing cycle due to the increased production of tuberous roots (92.5%), dry mass (125.0%), and starch (144.0%). These are important characteristics for the starch industry.…”
Section: Introductionmentioning
confidence: 95%
“…Cassava (Manihot esculenta), having originated from Brazil and being cultivated in over 90 countries, is a plant very tolerant to drought and low soil fertility, commonly grown and consumed by small farmers in areas of poor soils and where the weather conditions are often unfavorable to other cultures (Doretto, 1993;Sagrilo et al, 2002). However, it is one of the main economic sources of carbohydrates in the tropical regions, playing a key role in human and animal nutrition and in the industrial processing of flour and starch (Albuquerque et al, 2008).…”
Section: Introductionmentioning
confidence: 99%